Implikasi Hukum dan Psikologis Penerapan Praktik Outsourcing Berdasarkan Undang-Undang Cipta Kerja Terhadap Pekerja/Buruh - Sitanggang, Tio Theresia; Simanullang, R.A. Hotmartua; Ferencia, Viony (UKM Lembaga Penalaran dan Penulisan Karya Ilmiah Fakultas Hukum Universitas Hasanuddin, 2024)
The provisions in Article 64 of Law No. 13/2003 on Manpower regulate work agreements between companies that have the ability to hand over part of the execution of work to other companies through the mechanism of a work contract or the provision of worker/labor services, which is often referred to as an “outsourcing contract”. However, outsourcing schemes pose a great risk to workers/laborers, as indicated by legal uncertainty regarding the existence of outsourced workers/laborers and the increased possibility of job insecurity. Changes to the Manpower Law in Law No. 6 of 2023 on the Stipulation of Government Regulation in Lieu of Law No. 2 of 2022 still fail to meet the expectations of workers/laborers regarding the outsourcing system This research uses a normative legal research approach with the method of analyzing regulations in the Manpower Law and its comparison with the Cipta Kerja Law. The results of this study show that: firstly, national development aims to create welfare through employment, but outsourcing practices often harm workers by not guaranteeing their rights; secondly, changes to outsourcing-related regulations in the UUCK have cut worker protections, leading to uncertainty over working status and increased stress and anxiety that reduce worker performance; and thirdly, the many issues of outsourcing practices have led to a number of problems.